DYNAMICS OF CUSTOMER PARTICIPATION IN SUBSCRIPTION BUSINESS MODELS: CASE ANALYSIS AND IMPLICATIONS FOR SUSTAINABLE MARKETING STRATEGIES - Nida Garnida Fitrianti; Nazhira Nindya Padma Hanuun; Raden Roro Fatmasari (PT. Kreatif Indonesia Satu, 2024)
The dynamics of customer participation in subscription business models has become a major focus in modern marketing strategies in various industries. This research aims to investigate the implications of customer participation dynamics on the success of subscription business models, as well as to explore the ethical aspects involved in marketing practices driven by these dynamics. Using the qualitative research method of literature study, in-depth analysis was carried out on cases from various industries, including media, retail, technology and services. The research results show that the level of customer engagement, changes in customer preferences, response to promotions, customer satisfaction, and level of service utilization are key factors that influence customer participation in subscription business models. The ethical implications of marketing practices in subscription business models include transparency, fairness, and social responsibility towards customers. In developing sustainable marketing strategies, companies are advised to conduct regular audits of their marketing practices, ensure compliance with regulations and ethical standards, and involve customers in the decision-making process and development of new products or services. Thus, companies can build stronger relationships with their customers, increase loyalty, and achieve sustainable business growth in the long term.